Taksiran parameter genetik untuk pertumbuhan dan kelurusan batang uji keturunan Araucaria cunninghamii umur 5 tahun - Dedi Setiadi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
An open-pollinated progeny test of Araucaria cunninghamii was established in Bodowoso, East Java.The seeds were collected from 28 parent trees in 3 provenances in papua. The progeny test was arranged according to randomized Complete Block Design consisting of 28 families, 8 replications, 4 lines tree plot and spacing at 4 m x 3 m. At five years of age differences between provenances or families within provenance was significant for height, diameter and stem straightness. Heritability estimates for height, diameter and stem straightness were all moderate: (h2f – 0.44, h2i =0.11) for height, h2f – 0,36 h2i =0.12) for straightness). The genetic corrwelations between traits were strong and positive: 0.62 for height and diameter, 0.73 for diameter and straightness (rg=0.73) and height and straightness. The genetic gains from family selection with selection intensity of 70 % for height, diameter and stem straightness were 7.8 %, 2.5 %, and 9.7 % respectively, While those from individual selection with selection intensity of 10 % for height, diameter and stem straightness were 10.7 %, 4.6 % and 15.3 % respectively.